Nanochannel structures in W enhance radiation tolerance. (July 2018) - Qin, Wenjing; Ren, Feng; Doerner, Russell P.; Wei, Guo; Lv, Yawei; Chang, Sheng; Tang, Ming; Deng, Huiqiu; Jiang, Changzhong; Wang, Yongqiang
Abstract: Developing high performance plasma facing materials (PFMs) is one of the greatest challenges for fusion reactors, because PFMs face unprecedented harsh environments including high flux plasma exposure, fast neutron irradiation and large transmutation gas. Tungsten (W) is considered as one of the most promising PFMs. Rapid accumulation of helium (He) atoms in such environments can lead to the He bubbles nucleation and even the formation of nano- to micro-scale "fuzz" on W surface, which greatly degrade the properties of W itself. The possible ejection of large W particulates into the core plasma can cause plasma instabilities. Here, we present a new strategy to address the root causes of bubble nucleation and "fuzz" formation by concurrently releasing He outside of W matrix through the nano-engineered channel structure (nanochannels). Comparing to ordinary bulk W, nanochannel W films with high surface-to-volume ratios are found to not only delay the growth of He bubbles, but also suppress the formation of "fuzz" (less than a half of the "fuzz" thickness formation in bulk W). Molecular dynamic (MD) simulation results elucidate that low vacancy formation energy and high He binding energy in the nanochannel surface effectively help He release and affect He clusters distribution in W during He ion irradiation. Graphical abstract: Image 1